Alternating cycle pedagogy as an emancipating proposal in countryside education (Research, Society and Development, 2022)
The text now presented brings the epistemological contributions of a research in progress in the Master's Degree in Science and Humanities Teaching, Federal University of Amazonas. The goal is to make a historical contextualization of the object of study, reflecting on the act of educating for the liberation of the countryside men and women. The methodology used is qualitative and bibliographical, aiming to analyse the proposal of the Alternating Cycle Pedagogy in the Family Agricultural School. The partial results show that the teaching model of the alternance pedagogy emerged in France in 1935, constitutes an educational experience that seeks to break with the model of capitalist production, for the strengthening of alternatives based on ecology, emancipation of peasant identities and their agricultural territories. The proposal of the Alternating Cycle Pedagogy as an instrument of teaching and learning is inserted in rural education, based on the desires and struggles of individuals who have led diverse experiences of education aimed at the reality of life of the populations who live in rural contexts.